Paper platform for reflectometric determination of furfural and hydroxymethylfurfural in sugarcane liquor - Milani, Maria Izabel [UNESP]; Rossini, Eduardo Luiz [UNESP]; Castoldi, Karine [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier, 2017)
Cachaça is the popular name of sugarcane liquor obtained from fermented sugarcane mash broth. This is one of the most popular alcoholic beverages in Brazil and is gaining ground in the global market. One of the quality parameters established by Brazilian law is the sum of the concentrations of furfural and hydroxymethylfurfural, two compounds that give the beverage an unpleasant taste and have mutagenic potential. These two substances are usually determined by chromatographic techniques that employ toxic organic solvents that can be damaging to the health of the operator and to the environment. This paper describes the development of a new methodology to determine furfural and hydroxymethylfurfural in sugarcane liquor using a diffuse reflectance technique coupled with limited-area spot-testing on a paper platform. The new method presented LOQ values of 0.74 mg L− 1 for furfural and 1.27 mg L− 1 for hydroxymethylfurfural. Recoveries in the ranges 89.5–108% (furfural) and 96.3–106% (hydroxymethylfurfural) indicated that there was no significant influence of the matrix in determination of the analytes. The method was applied using eleven sugarcane liquor samples from different locations in Brazil.
Keywords: Diffuse reflectance spectroscopy; Furfural; Hydroxymethylfurfural; Sugarcane liquor